Electrospun cellulose fibres and applications - Wan Farahhanim Wan Fathilah; Rizafizah Othaman (Penerbit Universiti Kebangsaan Malaysia, 2019)
Cellulose fibres and nanofibres have gained interest because of the high strength and firmness, biodegradability and renewability. The enthusiasm in cellulose and its modification as cellulose-derivative has been exponentially expanding. This paper discuss on cellulose and its derivatives, and methods to produce cellulose fibres and nanofibres. Emphasis is given on electrospinning technique, the most utilised technique to produce cellulose fibres and cellulose nanofibres with ranging from nanometer to millimeter in diameter. It also summarises cellulose in terms of a matrix of cellulose, solvent, parameter electrospinning, fibre diameter and their perspective applications.